Cumulative knowledge and progress in human factors.[article]. - Procter, Robert W.
This review provides a cumulative perspective on current human factors research by first briefly acknowledging previous Annual Review articles. We show that several recent conceptual advances are an outgrowth of the information-processing approach adopted by the field and present several areas of current research that are built directly on prior work. Topics areas that provide fundamental tools for human factors analyses are summarized, and several current application areas are reviewed. We end by considering alternatives to the information-processing approach that have been proposed placing those alternatives in context. We argue that the information-processing language provides the foundation that has enabled much of the growth in human factors. This growth reflects a cumulative development of concepts and methods that continues today.